Research on Second Language: Offering New Alternative to Introduce Second Language to Children in Early Age through Youtube Channel - enni akhmad daud (ELT Worldwide: Journal of English Language Teaching, 2019)
This article is discussing about the children acquisition in second language. It is observing how a child acquires her second language through YouTube. It described the child age 3,7 years habit to watch video through YouTube. The daily notes were taken to see the child’s words, sentences, and also reaction after watching the video intensively for two months. The research observation result shown that a child starts her acquiring by perceiving the language through silent period. She needs 3-5 times to watch a video, and then she is able to imitate words and sentences in video, even though her pronunciation is not fluency yet. Moreover, she does not really understand about the meaning of the words or sentences. It is indicated that the children age 3,7 years old still has difficulties to understand the beyond meaning of the words or sentences. The implication of this research is to show the stages of children in acquiring their second language which is similar to their first language acquisition. Therefore, teaching and learning second language should not be different from teaching and learning first language.